Skating toward Americanization: The Transformation of Katarina Witt throughout the 1980s. Issue 2 (1st June 2019) - Lim, Wesley
Abstract : At the 1987 World Figure Skating Championship, Katarina Witt skated to instrumental music from West Side Story playing the role of Maria. But how could her performance to Broadway show tunes be in line with SED ideology? Through histoire croisée— establishing multiple intersections with different cultures and tracing their continuing effects—this article examines how Witt's, her coach Jutta Müller's and choreographer Rudy Suchy's privileged exposure to Western culture through dance, music, film, experiences abroad, and other skaters' choreography and costuming inspired reappropriated manifestations through an East German lens into the packaging of Witt's skating programs in the 1980s. Using television broadcasts, I analyze the gradual to overt Americanization of her programs as her government loosened its grips by granting her more artistic freedom.